Labor productivity and the law of decreasing labor content - Peter Flaschel; Reiner Franke; Roberto Veneziani (University of Massachusetts, Department of Economics, 2010)
This paper analyzes labor productivity and the law of decreasing labor content (LDLC) originally formulated by Farjoun and Machover (1983). First, it is shown that the standard measures of labor productivity may be rather misleading, owing to their emphasis on monetary aggregates. Instead, the conventional classical-Marxian labor values provide the theoretically and empirically sound measures of labor productivity. The notion of labor content and the LDLC are therefore central in order to understand the dynamics of capitalist economies. Second, some rigorous theoretical relations between different forms of profit-driven technical change and productivity are derived in a general input-output framework with fixed capital, which provide deterministic foundations to the LDLC. Third, the main theoretical propositions are analyzed empirically based on a new dataset of the German economy.
Keywords: B51; D57; O33; C67; 330; labor productivity; law of falling labor content; technical change; labor values; Input-Output analysis